2023
DOI: 10.3847/1538-4357/acf373
|View full text |Cite
|
Sign up to set email alerts
|

Forming Gas Giants around a Range of Protostellar M-dwarfs by Gas Disk Gravitational Instability

Alan P. Boss,
Shubham Kanodia

Abstract: Recent discoveries of gas giant exoplanets around M-dwarfs from transiting and radial velocity surveys are difficult to explain with core-accretion models. We present here a homogeneous suite of 162 models of gravitationally unstable gaseous disks. These models represent an existence proof for gas giants more massive than 0.1 Jupiter masses to form by the gas disk gravitational instability (GDGI) mechanism around M-dwarfs for comparison with observed exoplanet demographics and protoplanetary disk mass estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
0
9
1
Order By: Relevance
“…Keeping this possibility in mind, it is nevertheless curious that migration on timescales as rapid as t m = 10 4∼5 yr is a consistent feature of hydrodynamic simulations modeling giant planet formation via the gravitational instability mechanism (Baruteau et al 2011;Stamatellos 2015;Rowther & Meru 2020). Though this pathway has in recent years attracted criticism, recent advances on the theoretical front (e.g., Boss & Kanodia 2023;Longarini et al 2023) together with intriguing discoveries from observations (e.g., Morales et al 2019;Weber et al 2023) are an indication that it deserves further study. We also observed that high initial giant multiplicities can help offset the need for rapid migration, as evidenced by the strong match between the N4T6K1 simulations, which had slow migration with t m = 10 6 yr, and the CLS subsample.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping this possibility in mind, it is nevertheless curious that migration on timescales as rapid as t m = 10 4∼5 yr is a consistent feature of hydrodynamic simulations modeling giant planet formation via the gravitational instability mechanism (Baruteau et al 2011;Stamatellos 2015;Rowther & Meru 2020). Though this pathway has in recent years attracted criticism, recent advances on the theoretical front (e.g., Boss & Kanodia 2023;Longarini et al 2023) together with intriguing discoveries from observations (e.g., Morales et al 2019;Weber et al 2023) are an indication that it deserves further study. We also observed that high initial giant multiplicities can help offset the need for rapid migration, as evidenced by the strong match between the N4T6K1 simulations, which had slow migration with t m = 10 6 yr, and the CLS subsample.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work has shown that stellar irradiation at wide orbits (where the disk is optically thin) can inhibit gravitational collapse in disks 30% in mass ratio (Cadman et al 2020;Haworth et al 2020;Mercer & Stamatellos 2020). However, recently, Boss & Kanodia (2023) ran a suite of formation models to show the feasibility of giant planet formation at closer separations (<5 au), where the disk is optically thick and hence more impervious to the effects of stellar irradiation. This enables the formation of giant planets with lower disk-to-star mass ratios of ∼10%.…”
Section: Planet Formation and Migrationmentioning
confidence: 99%
“…Haworth et al (2020) presented a range of SPH models for massive disks around M-dwarf stars to show the difference between disk-to-star mass ratios for disks that remain axisymmetric, produce spiral arms, or fragment into clumps. Boss & Kanodia (2023) perform GI-based population synthesis to quantify the frequency with which GEMS can be formed around a range of stellar masses ranging from 0.1 to 0.5 M e and disk-to-star mass ratios of 0.05-0.3. These mass ratios are consistent with those seen in Class 0/I protostellar samples from the Very Large Array (Tychoniec et al 2018(Tychoniec et al , 2020Xu 2022;Fiorellino et al 2023).…”
Section: Formation During Protostellar Phasementioning
confidence: 99%